Experiências estéticas na cidade colonial: poesia slam e a formação de sujeitos políticos em Natal/RN - Oliveira, Olga Maria Hawes Fernandes de (2025)
Since the 1990s, the peripheral literature movement has emerged in Brazil, characterized by the prominence of artists from urban peripheries as a response to segregation in modern cities. Among these, resistance poetry, or slam poetry, has been gaining increasing followers. Poetry battles assess poems based on their political, identity, lyrical, and performative qualities, and have spread worldwide, transforming the cultural landscape, previously closed off to elites, by incorporating diverse social profiles into literature. In the city of Natal/RN, slams have been gaining visibility since 2019, introducing young artists into the political-cultural scene marked by the legacies of colonialism and clientelism system established since the hereditary captaincy period in Rio Grande do Norte. It is in this context that this study arises, with the objective of investigating the aesthetic experiences of peripheral poets in relation to politics in Natal. The Slam Rima Central, one of the pioneers of the slam culture in the city, was chosen as the focus of this study. The research was guided by the notions of aesthetic experience/lived experience in Vygotsky and their incorporation into Jacques Rancière's notion of politics, also in dialogue with the postcolonial feminisms of Judith Butler and Patricia Hill Collins. The approach to the field/topic occurred through bibliographic review, immersion in slam events by observation participant, as well as field diary records. Two interviews were also conducted with the organizers of the slam, the slammasters. The results were organized into three chapters that aim to construct scenes of dissent, inspired by Rancière's scene method. The first chapter discusses the relationship between slam poetry and politics, addressing the production of sensitive regimes in the literary field. In the second, we introduce a slam night and the spatiotemporal disruptions mobilized in the urban setting, investigating the po(etic) practices established by the movement. In the final chapter, we analyze the poetic-musical manifesto of one of the interviewees, considering the litigation surrounding the revision process of the document that determined Natal’s Master Plan. The conclusion is that slams are spaces of poetic experimentation that mobilize the subversion of identities and can foster the emergence of political subjects. Collective Rima Central fosters a space-time of life potentialization, and an aesthetic community responsible for producing the common dissensus in police-like spaces, as well as promoting cultural and identity self-valorization, forming networks of alliances and support crucial for political emancipation and the celebration of peripheral and Potiguar aesthetic expression.